COMPETENCY AND WORK DISCIPLINE ANALYSIS OF THE PERFORMANCE OF THE STATE CIVIL APPARATUS IN THE SERVICE HEALTH OF WEST KUTAI REGENCY - Weda Weda; Yonathan Palinggi; Ida Bagus Made Agung Dwi Jatenaya (International Journal Labs, 2022)
The success of local government administration cannot be separated from the performance of the State Civil Apparatus (ASN) which is supported by good competence and work discipline in carrying out their job responsibilities. This study aims to determine the extent of the influence of competence and work discipline on the performance of the State Civil Apparatus at the Health Office of West Kutai Regency. Employee performance is the achievement of an employee's work by carrying out the tasks assigned to him in accordance with his responsibilities. Competence is a person's ability to carry out a job based on skills and knowledge and supported by a good work attitude. While work discipline is an attitude of willingness and willingness of a person to obey and obey the regulations that apply in the organization. This research is included in the category of causal associative research using a quantitative approach. The research method used is multiple regression analysis. The study population was 39 State Civil Apparatus at the Health Office of West Kutai Regency with a sample of 37 people. The results obtained in this study are that there is a significant influence between the variables of competence (X1) and work discipline (X2) simultaneously on employee performance (Y) with the acquisition of an F value of 40.793 which is greater than F table (3.27).